Pengaruh Selfefficacy, Dukungan Orang Tua, Teman Sebaya dan Biaya Pendidikan terhadap Keputusan Memilih Program Studi di Universitas PGRI Sumatera Barat - Adela Puspita; Yesmira Syamra; Jolianis Jolianis (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to determine the effect of Self-Efficacy, parental support,peers, tuition feeson the decision to choose an accounting education study program at Universitas PGRI Sumatera Barat. The analysis technique used descriptive analysis and inductive analysis, namely multiple linear regression analysis with the help of Eviews12 data processing tools, the coefficient of determination (R2) and hypothesis testing using the T test and F test The results of the study: 1) There is a significant influence between self efficacy (X1) on the decision to choose a study program (Y) with a coefficient value of 0.455, tcount of 3.202> t table of 1.659. 2) There is a significant influence between parental support (X2) on the decision to choose a study program (Y) with a coefficient value of 0.261, the tcount value of 3.183> t table of 1.659. 3) There is a significant influence between peers (X3) on the decision to choose a study program (Y) with a coefficient value of 0.327, the tcount value of 3.155> ttable of 1.659. 4) There is a significant influence between education costs (X4) on the decision to choose a study program (Y) with a coefficient value of 0.181, the tcount value of 2.063> t table of 1.659. 5) There is an effect of self efficacy (X1), parental support (X2), peers (X3), and tuition fees (X4) simultaneously on the decision to choose a study program (Y) with an Fcount value of 27.83> Ftable 2.46.